PENDIDIKAN ISLAM DAN KERUKUNAN ANTARETNIS: PERAN MUHAMMADIYAH DALAM MENJEMBATANI MASYARAKAT MUSLIM DAYAK DAN MASYARAKAT BANJAR DI KALIMANTAN SELATAN - Z, Syarif Hidayatullah; Jamalie, Zulfa (IAIN Bone, 2025)
This study aims to explore the role of Muhammadiyah in fostering interethnic harmony between the Muslim Dayak and Banjar communities in South Kalimantan through Islamic education. Utilizing a qualitative descriptive approach with a case study method, the research relies primarily on document analysis, supported by limited informal interviews. The data reveal that Muhammadiyah employs daâ€™wah bil hal -a practical and socially responsive approach- as a key strategy to empower Dayak converts and promote social interaction with the Banjar community. Through inclusive educational programs and culturally sensitive outreach, Muhammadiyah has contributed to building intercultural dialogue, enhancing social solidarity, and supporting grassroots integration in a multiethnic society.Â